1994
DOI: 10.1590/s0037-86821994000400006
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilidade do Triatoma infestans a diferentes cepas de Trypanosoma cruzi isoladas de pacientes chagásicos do Triângulo Mineiro

Abstract: No presente trabalho avaliou-se a susceptibilidade do Triatoma infestans a sete cepas de Trypanosoma cruzi, isoladas e adaptadas em camundongos, provenientes de pacientes chagásicos do Triângulo Mineiro. Alimentou-se um total de 2 0 0 triatomíneos sobre camundongos infectados, na fase aguda, com as diferentes cepas e a cada 30 dias durante 5 meses, realizouse as leituras pelos métodos da compressão e dejeção espontânea. A positividade do T . infestans frente as diferentes cepas fo i de 62,08% acompanhado de um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…muximus and that, maintenance of a P. megistus colony in the laboratory is easier (fast development, slow locomotion, low mortality and easy to breed under changing enviroments). Nirschl et al (1994) analized the susceptibility of T. irzfestans infected by seven strains of T. cruzi derived from chagasic patients from TriGngulo Mineiro, MG, and concluded that this species had low susceptibility, which could explain the low rates of infectivity in xenodiagnosis in the same geographical area.…”
Section: Resultsmentioning
confidence: 99%
“…muximus and that, maintenance of a P. megistus colony in the laboratory is easier (fast development, slow locomotion, low mortality and easy to breed under changing enviroments). Nirschl et al (1994) analized the susceptibility of T. irzfestans infected by seven strains of T. cruzi derived from chagasic patients from TriGngulo Mineiro, MG, and concluded that this species had low susceptibility, which could explain the low rates of infectivity in xenodiagnosis in the same geographical area.…”
Section: Resultsmentioning
confidence: 99%